Respuesta :
Answer:
-3
Step-by-step explanation:
Anything that is negative multiplied by a negative is a positive so knowing this, you can multiply -3*-3=9 or divide 9/-3=-3
Hope this helps
<> Anna <>
Answer:
The answer to linear equation 9t=-3 is t = - (1/3)
Step-by-step explanation:
9t=-3
Solving for t: Dividing both sides of the equation by 9:
9t/9=-3/9
t=-(3/9)
Simplifying the fraction on the right side of the equation dividing the numerator and denominator by 3:
t = - (3/3) / (9/3)
t = - (1/3)